A Conceptual Study of Maqasid al-Sharia in Usul al-Fiqh and Its Implementation in Contemporary Islamic Law - Hera Madhani Priyasdanto; Kuni Nurol Choiriyah (MLIJo: Journal of Law and Islamic Thought, 2026)
This paper discusses the concept of Maqasid Syariah, its classification, and its relevance in contemporary Islamic law. The aim of this study is to explain the theoretical foundations of Maqasid Syariah, its evolution from classical to modern times, and the importance of Maqasid in developing Islamic law that is responsive to the challenges of contemporary issues. By focusing on the five key goals of Islamic law protecting religion, life, intellect, lineage, and property this paper explores how Maqasid Syariah serves as a philosophical foundation for dynamic and contextual applications of Islamic law, and its implementation in various fields such as economics, healthcare, education, and environmental protection. The paper also discusses the challenges faced in the implementation of Maqasid Syariah in pluralistic social and political contexts, as well as the need for strengthening ijtihad institutions in applying Maqasid Syariah principles in the modern era.